Frequency of TTG Positivity in Diarrhea Predominant IBS Patients at Peshawar, Pakistan : TTG Positivity in Diarrhea Predominant IBS Patients - Khan, Bughdad; Khan, Muhammad Shadab Aslam; Naeem, Awais; Naim, Fahad; Utmani, Nizamuddin; Safiullah, . (Pakistan Journal of Health Sciences, 2024)
Irritable Bowel Syndrome is abdominal discomfort and alterations in bowel habits without an identifiable organic cause. Objective: To determine the frequency of tissue transglutaminase positivity in diarrhea-predominant IBS patients. Methods: This cross-sectional study was done from 1st January 2021 to 30th July 2021 in the Medicine department of Khyber Teaching Hospital, Peshawar, Pakistan. Patients of either gender aged between 18-60 years presenting in the medical outpatient department with diarrhea-predominant irritable bowel syndrome. Diarrhea-predominant irritable bowel syndrome was defined as a patient who fulfilled the Rome-IV criteria for irritable bowel syndrome with ≥2 of the features. Tissue transglutaminase antibodies were done for all patients and tissue transglutaminase positivity was defined as anti-tissue transglutaminase IgA or IgG antibody levels ≥10 AU/ml on laboratory tests performed by the chemi-luminescence immunoassay technique. Results: In a total of 96 patients, 59 (61.5%) were male. The mean age, weight, and duration of diarrhea were 37.64 ± 6.28 years, 81.48 ± 7.70 kg, and 11.67 ± 3.81 months, respectively. The tissue transglutaminase positivity was seen in 12 (12.5%) of patients. Duration of disease above 6 weeks was found to have a significant association with tissue transglutaminase positivity (p<0.001) as all tissue transglutaminase-positive patients had a duration of disease above 6 months. Conclusions: It was concluded that the frequency of tissue transglutaminase positivity was high in diarrhea-predominant irritable bowel syndrome patients. Screening for celiac disease in irritable bowel syndrome patients can be worth considering especially in cases with relatively longer duration of irritable bowel syndrome diarrhea predominant symptoms.